Heated, humidified high-flow nasal cannula vs. nasal CPAP in infants with moderate respiratory distress - Adhi Teguh Perma Iskandar; Risma Kerina Kaban; Mulyadi M Djer (Indonesian Pediatric Society, 2019)
Background Respiratory distress is the most common cause of morbidity in premature babies in the delivery room. Nasal continuous positive airway pressure (nCPAP) is widely used as the preferred modality of treatment, although it may cause nasal trauma. Heated, humidified high-flow nasal (HHHFN) cannula is an alternative oxygen therapy, yet the safety and efficacy has not been widely studied. Objective To compare the safety and efficacy of HHHFN and nCPAP in premature babies with gestational age > 28 to < 35 weeks and moderate respiratory distress. Methods We conducted a randomized, non-inferiority, clinical trial using HHHFN vs. nCPAP as a treatment for moderate respiratory distress within 72 hours after they had been used. The efficacy endpoints were treatment failure, length of device use, length of Kangaroo Mother Care (KMC), and full enteral feeding time. Safety assessment included pain score, nasal trauma, and systemic complications. Results No differences were found in terms of incidence of endotracheal intubation within < 72 hours of HHHFN (20%) compared to nCPAP (18%) (P=0.799). However, there was a significant difference in moderate nasal trauma in nCPAP (14%) compared to HHHFN (0%)(P=0.006). There were no significant differences of blood gas analysis results, full enteral feeding time, length of KMC, length of device use, and rate of complications (bronchopulmonary dysplasia/BPD, intraventricular hemorrhage/IVH, patent ductus arteriosus/PDA, necrotizing enterocolitis/NEC and late onset neonatal sepsis/LONS) between the nCPAP and HHHFN groups. Conclusion The HHHFN is not inferior to nCPAP in terms of the safety and efficacy as primary non-invasive therapy in premature babies of gestational age > 28 to < 35 weeks with moderate respiratory distress . Compared to nCPAP, HHHFN induced lower nasal trauma.